EVALUASI INPUT CAPAIAN CASE DETECTION RATE (CDR) TB PARU DALAM PROGRAM PENANGGULANGAN PENYAKIT TB PARU (P2TB) PUSKESMAS TAHUN 2012 (STUDI KUALITATIF DI KOTA SEMARANG) (Unnes Journal of Public Health, 2015)
CDR of pulmonary TB Semarang in 2012 amounted 70.22% with 109% the highest health centers and 11% the lowest. The purpose of this study to determine the performance evaluation CDR of TB in TB Pulmonary Disease Reduction program (P2TB) at Semarang City Health Center in 2012. This research is qualitative. Informant is research program P2TB holders, laboratory personnel, administration head and head health center at 6 CDR > 75% and 6 CDR < 75%. Techniques of data collection with in-depth interviews, observation, and documentation. The instruments used were interview, observation, and documentation sheets. The results showed component at health centers with CDR â‰¥ 75% in accordance with provisions Health Ministry of Indonesia is duty and responsibility of the holder P2TB programs, laboratory staff, and head health centers, funding, networking suspected, diagnosis, and reporting. The health center with CDR <75%, which in accordance with provisions of the components Health Ministry of Indonesia is duty and responsibility the head of community health centers, funding, and diagnosis. Suggestions to holders P2TB programs and laboratory personnel that improve performance in achieving pulmonary TB CDR, administration leaders to improve coordination with holder program, the health center leaders to increase motivation by rewarding performance officers.